Platelet Activating Factor Contributes to Vascular Leak in Acute Dengue Infection - Jeewandara, Chandima; Gomes, Laksiri; Wickramasinghe, N.; Gutowska-Owsiak, Danuta; Waithe, Dominic; Paranavitane, S. A.; Shyamali, N. L. A.; Ogg, Graham S.; Malavige, Gathsaurie Neelika (PLOS Neglected Tropical Diseases, 2015)
Background Although plasma leakage is the hallmark of severe dengue infections, the factors that cause increased vascular permeability have not been identified. As platelet activating factor (PAF) is associated with an increase in vascular permeability in other diseases, we set out to investigate its role in acute dengue infection. Materials and Methods PAF levels were initially assessed in 25 patients with acute dengue infection to determine if they were increased in acute dengue. For investigation of the kinetics of PAF, serial PAF values were assessed in 36 patients. The effect of dengue serum on tight junction protein ZO-1 was determined by using human endothelial cell lines (HUVECs). The effect of dengue serum on and trans-endothelial resistance (TEER) was also measured on HUVECs. Results PAF levels were significantly higher in patients with acute dengue (n = 25; p = 0.001) when compared to healthy individuals (n = 12). In further investigation of the kinetics of PAF in serial blood samples of patients (n = 36), PAF levels rose just before the onset of the critical phase. PAF levels were significantly higher in patients with evidence of vascular leak throughout the course of the illness when compared to those with milder disease. Serum from patients with dengue significantly down-regulated expression of tight junction protein, ZO-1 (p = 0.004), HUVECs. This was significantly inhibited (p = 0.004) by use of a PAF receptor (PAFR) blocker. Serum from dengue patients also significantly reduced TEER and this reduction was also significantly (p = 0.02) inhibited by prior incubation with the PAFR blocker. Conclusion Our results suggest the PAF is likely to be playing a significant role in inducing vascular leak in acute dengue infection which offers a potential target for therapeutic intervention.